2019
DOI: 10.1080/0886022x.2019.1628780
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxic kidney injury

Abstract: Substances toxic to the kidney are legion in the modern world. The sheer number and variety, their mutual interactions and, metabolism within the body are a challenge to research. Moreover, the kidney is especially prone to injury owing to its physiology. Acute kidney injury (AKI) induced by poisonous or primarily nephrotoxic substances, may be community acquired with ingestion or inhalation or nosocomial. Many nephrotoxic plants, animal poisons, medications, chemicals and illicit drugs can induce AKI by varyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 129 publications
0
34
0
1
Order By: Relevance
“…These changes can further reduce renal perfusion and induce cell injury or death. Moreover, many anti-tumor drugs had potential nephrotoxicity [ 28 ]. It was reported that 80.1% of cancer patients had received such drugs [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…These changes can further reduce renal perfusion and induce cell injury or death. Moreover, many anti-tumor drugs had potential nephrotoxicity [ 28 ]. It was reported that 80.1% of cancer patients had received such drugs [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lysosomal proximal tubulopathy with abnormal enlarged dysmorphic lysosomes containing dispersed dark electron-dense aggregates, under light and electron microscopy, indicating a toxin-induced proximal tubular nephropathy in CKDu patients [ 6 , 43 ]. Indeed, varying levels of heavy metals such as mercury, cadmium and lead, arsenic, vanadium, and other agrochemical constituents as well as other nephrotoxic compounds have been found in soil, drinking water, and food in CKDu endemic regions [ 29 , 44 , 45 ]. In contrast, in a recent study in CKDu prevalent areas in Sri Lanka, analysis of urine, hair, and renal tissue samples did not provide evidence to support cadmium or arsenic toxicity in CKDu patients.…”
Section: Etiology Of Ckdumentioning
confidence: 99%
“…To assess the potential of using TFCH for detecting nephrotoxins, we chose to focus on two standard cellular models for assessing small molecule toxicity: porcine kidney proximal tubule (LLC-PK1) cells and distal tubule-derived Madin-Darby Canine Kidney (MDCK) cells [12,13]. We established our assay in these cell lines using SFM, menadione or hydrogen peroxide (H2O2) as stress induction models.…”
Section: A Sensitive Fluorescent Assay For Screening Chemical Toxin-imentioning
confidence: 99%